Comparative study of the effect of low-dose versus high-dose aspirin on the retina of aged male albino rats: a histological and immunohistochemical study. Issue 3 (September 2016) - El-Nefiawy, Nagwa E.; Hanna, George F.B.
Abstract : Background: Aspirin is a very popular drug worldwide. Recent studies have suggested that long-term aspirin use might be linked to wet-type acute macular degeneration. Aim: This study was undertaken to investigate and compare the effects of chronic daily intake of low-dose versus high-dose aspirin on the structure of the retina in aged male albino rats for the first time. Materials and methods: Twelve-month-old male albino rats were assigned to three groups: control, low-dose (2mg/kg) aspirin, and high-dose (10mg/kg) aspirin. The rats were given oral aspirin daily for 1 month. At the end of the experiment, the animals were euthanized and their eyes were enucleated and processed for paraffin blocks. Some of the paraffin sections were stained with H&E, whereas others were immunohistochemically stained with TUNEL, CD31, and glial fibrillary acidic protein markers. Histomorphometric count of ganglion cells, outer nuclear layer cells, CD31-positive cells, and TUNEL- positive cells was carried out using image analysis software. Statistical analysis of cell counts was performed. Results: This study showed that chronic aspirin administration induced many degenerative changes in the aged rat retina. Stratification and vascularization of the retinal pigment epithelium was detected in addition to disruption of the photoreceptors. Apoptotic changes were detected in the inner nuclear layer and ganglion cell layer with significant decrease in cell number, which was pronounced with the high dose of aspirin. An increase in glial fibrillary acidic protein immunoreactivity of Müller cells was detected, especially in the high-dose group. Also, retinal neovascularization was clearly detected in the high-dose aspirin group. Conclusion: Chronic aspirin intake is likely to produce retinal degenerative changes in aged male rat retina. High-dose aspirin was more detrimental than low dose. Results of the present experiment confirmed some clinical observations that chronic aspirin use is associated with retinal degenerative changes.